Education Beyond Blocks: Syntax and Semantics. - Benjamin Shapiro, R.; Ahrens, Matthew (Communications of the ACM, 2016)
The author shares insight on the feasibility of blocks-based structured editing to become a standard for industrial and academic language developers. He suggests the potential of block and text hybrid environments to improve the efficiency and usability of general purpose programming. He highlights efforts on transitioning blocks to text focused on systems building and discusses the design of programming tools that provide exposure to the semantics of general purpose programming environment.